Spiradiclis scorpiura (Rubiaceae), a new species from Guangxi, China - You Nong; Li-Qun Lei; Lei Wu; Qi-Min Hu; Ying-Jing Li; Xin-Cheng Qu; Chuan-Gui Xu; Gui-Yuan Wei (PhytoKeys)
Spiradiclis scorpiura (Rubiaceae), a new calcareous species found in Guangxi, China, is described and illustrated. This new species is similar to S. coccinea, S. scabrida, and S. purpureocaerulea in having pubescent stems and subglobose capsules, but it is easily distinguished by its cincinnous inflorescence and its triangular, 1–2 mm long, pubescent bracteoles. According to the IUCN criteria, it is considered Data Deficient (DD) until more information becomes available. Photographs, an illustration, a distribution map, and a comparative table with the most similar species are provided.